2015
DOI: 10.1108/jedt-12-2012-0056
|View full text |Cite
|
Sign up to set email alerts
|

Compressive behaviour of polypropylene filled with iron ore tailings

Abstract: Purpose – This paper aims to produce iron ore tailings reinforced polypropylene composites (ITR-PPCs) from conventional compo-casting (CC) and a proposed compo-indirect squeeze casting (C-ISC) processes. It intends to quantify the compressive behaviour of ITR-PPC with respect to production process, iron ore tailings volume and particle size inclusion in polypropylene (PP) through controlled material and compressive testing. The study aims to provide useful information on possibility of the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It can be concluded from Figure 3 that, the presence of IP reinforcement in the RPP matrix raises the composite strength and the modulus of elasticity. Therefore, the effect of adding of the IP into the polymeric on the tensile properties of the composites is of particular interest for special jobs like plastic RPP RPP+10%IP RPP+20%IP RPP+30%IP magnetics goods (mobile telephone covers, fused deposition modelling) [2][3][4][5][6][7][8][9][10][11]. However, the increasing of the UTS of the RPP with the IP, and the advantages of the magnetism and the conductivity, the process complexity, the increasing in the weight of the products which is main problem, and also cost must be taken into consideration.…”
Section: Results Of the Tensile Testmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded from Figure 3 that, the presence of IP reinforcement in the RPP matrix raises the composite strength and the modulus of elasticity. Therefore, the effect of adding of the IP into the polymeric on the tensile properties of the composites is of particular interest for special jobs like plastic RPP RPP+10%IP RPP+20%IP RPP+30%IP magnetics goods (mobile telephone covers, fused deposition modelling) [2][3][4][5][6][7][8][9][10][11]. However, the increasing of the UTS of the RPP with the IP, and the advantages of the magnetism and the conductivity, the process complexity, the increasing in the weight of the products which is main problem, and also cost must be taken into consideration.…”
Section: Results Of the Tensile Testmentioning
confidence: 99%
“…Onitiri and S.M. Adedayo [10] produced iron ore tailings reinforced PP composites from conventional compo-casting and a proposed compoindirect squeeze casting processes. Their study aims to provide useful information on possibility of the use of iron ore tailings reinforced PP for compressive applications which will culminate to judicious use of iron ore tailings that is been piled up as waste material at the iron ore beneficiation sites.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microfine iron tailings have been researched as a filling for thermoplastic because of their fine particle size, high stiffness and similar composition to that of clay minerals. Adedayo et al [ 31 ] prepared iron ore tailing–polypropylene composites. It was found that increasing the filling volume of IOT increased the impact strength of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Thus, several types of research are incorporated to enhance the wear-resistant behavior of PTFE using the addition of suitable filler materials (reinforcing materials), mainly nano particulates and fiber particles. [9] The influence of reinforcing materials mainly depends on the crystalline structure, size, shape, dispersion degree, and so forth. Normally, the filler particles, namely, bronze, carbon, graphite, glass, and alumina are utilized to enhance the tribological nature of PTFE.…”
Section: Introductionmentioning
confidence: 99%